Omega-3 index level in the adult population of Ukraine and its potential association with cardiovascular risk: a pilot study - Pylypenko, D.; Borshch, D.; Miakishev, O.; Talalaiev, K.; Babiienko, V.; Shanyhin, A. (Journal of Education, Health and Sport, 2026)
Cardiovascular diseases remain the leading cause of mortality worldwide and in Ukraine, necessitating the search for novel biomarkers for more accurate cardiovascular risk assessment. One of the promising indicators is the omega-3 index, which reflects the total content of eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) in erythrocyte membranes and characterizes the long-term omega-3 status of the body. Low omega-3 index values are associated with an increased risk of cardiovascular events, whereas optimal levels may exert a cardioprotective effect. Aim of the study. To assess the omega-3 index level in the adult population of Ukraine and analyze its relationship with body mass index (BMI) as one of the cardiometabolic risk factors. Materials and Methods. The study included 50 participants, among whom there were 19 men (38.0%) and 31 women (62.0%). The mean age of the participants was 44.08 ± 15.80 years. The study had an observational analytical design. Anthropometric parameters (height and body weight) with subsequent BMI calculation, as well as omega-3 index levels, were assessed in all participants. Statistical analysis was performed using descriptive statistics and Pearson correlation analysis. Results were considered statistically significant at p < 0.05. Results. In the overall sample, the mean BMI was 26.84 ± 4.72 kg/m², corresponding to overweight status, while the mean omega-3 index level was 5.62 ± 1.48%, which is considered suboptimal. In the obesity group, the mean omega-3 index was significantly lower compared to individuals with normal body weight (4.71 ± 1.12% vs. 6.48 ± 1.37%, p < 0.01). Correlation analysis demonstrated a strong inverse relationship between BMI and omega-3 index (r = -0.91; p < 0.001). In gender-stratified analysis, the negative correlation persisted both in men (r = -0.95; p < 0.001) and women (r = -0.89; p < 0.001). Additionally, a gradient decrease in omega-3 index with increasing BMI was observed (p for trend < 0.001). No statistically significant effect of age on omega-3 index levels was identified. Conclusions. The obtained results indicate a statistically significant inverse relationship between BMI and omega-3 index in the adult population. An increase in BMI is associated with lower omega-3 fatty acid levels, which may reflect the role of adipose tissue and nutritional status in the development of cardiometabolic risk. The identified dose-dependent relationship highlights the potential value of the omega-3 index as an additional marker for cardiovascular risk assessment and a promising target for nutritional prevention strategies.